Perancangan Sistem Informasi Toko Pak Kusno Sidorukun Untuk Mempermudah Jual Beli Barang - Putri, Jossie Mutiarani; Azery Althaf, Naufal; Frandipa, Sobri; Reyan Irfandra, Muhammad; Maulana Akbar, Riski; Fajar Surya, Rizky (LPPM Universitas Nias Raya, 2024)
Modern digital life relies heavily on information systems (IS) to manage data efficiently, make better decisions, and increase productivity. Mr. Kusno's shop faces problems of goods management, finance, and product promotion. This research designs a customized information system to solve those problems, such as easier digital transaction recording, more optimized goods management, and better financial management. The implementation of this system is expected to increase the efficiency and competitiveness of Toko Pak Kusno. The development method used is the waterfall method, which ensures each step is carried out sequentially from analysis, design, implementation, to system testing. The results showed efforts in designing an information system that can improve the operational efficiency and service quality of Toko Pak Kusno in buying and selling goods and store management.